a+(-1.6)=-3.7

Simple and best practice solution for a+(-1.6)=-3.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for a+(-1.6)=-3.7 equation:


Simplifying
a + (-1.6) = -3.7
a + -1.6 = -3.7

Reorder the terms:
-1.6 + a = -3.7

Solving
-1.6 + a = -3.7

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '1.6' to each side of the equation.
-1.6 + 1.6 + a = -3.7 + 1.6

Combine like terms: -1.6 + 1.6 = 0.0
0.0 + a = -3.7 + 1.6
a = -3.7 + 1.6

Combine like terms: -3.7 + 1.6 = -2.1
a = -2.1

Simplifying
a = -2.1

See similar equations:

| 5+6=-16 | | 7q-6q=-18 | | 3v-24=-2(v+7) | | 3-2(x+5)=5(4x) | | 6m+(-m)=-20 | | 2+-2w=6 | | (70)=-8x-106 | | (5)=3x-7 | | 7x+58=3x+22 | | 2y-7=7 | | (14)=-4x+50 | | 7x+1=7x^2-1 | | 4/5x*(-2/10)=1 | | f+0.2=-3 | | kx^2+(k-3)x=1 | | (-80)=-1.3x+20 | | -2x+1=x+10 | | 4/5x(-2/10)=1 | | -x/6-5 | | (16)=25/6x-34 | | 7/6=v/9 | | 3x(4x+5y)=23 | | 2.712=2X+6.78X | | 2(5x+6)=22 | | 2k-2k+4k=20 | | 5.4(4+3x)-9.6=12 | | 2(x-1)+3x+4=2-[5(x-1)-2(1-2x)-1] | | y-2=9(x+10) | | 10/5=x/7 | | 1/2(20) | | 0.8=20*x | | 4x^2-6=1-12x |

Equations solver categories